Method for preparing hydrogel with strain sensing performance from Pickering emulsion with stable xylan nanocrystals
By using the combination of xylan nanocrystal-stable Pickering emulsion with PVA, sodium tetraborate and TMPTA, a composite hydrogel with strain sensing performance was prepared, which solved the problem of the failure to develop a hydrogel sensor with high sensitivity and high tensile sensitivity in the prior art, and achieved efficient strain-resistance effect and mechanical performance improvement.
Patent Information
- Application Number
- CN202411875300.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-04
AI Technical Summary
In the prior art, xylan nanocrystals are not used to prepare composite hydrogels with strain-resistance effects, which limits the development of hydrogel sensors with high sensitivity and high tensile sensitivity.
Hydrogels with strain sensing properties were prepared by using xylan nanocrystal-stabilized Pickering emulsion combined with PVA, sodium tetraborate and TMPTA. The method includes forming XyNC@pTMPTA microsphere emulsion and introducing a dynamic crosslinking network through borate bonds to enhance the three-dimensional framework stability and deformation resistance of the hydrogel.
It achieves a strain-resistance effect with high sensitivity and high tensile sensitivity, improves the mechanical properties and conductive sensitivity of the hydrogel, and is suitable for the development of flexible sensors.
Smart Images

Figure CN119552387A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a novel functional material, and in particular to a method for preparing a composite hydrogel with strain-resistance effect. The hydrogel can be used to prepare a hydrogel strain sensor with high sensitivity and high stretch sensitivity. Background Art
[0002] Polysaccharide nanocrystals are crystalline rigid nanoparticles extracted from biomass by strong acid hydrolysis or mechanical grinding. They have unique properties such as high aspect ratio, renewability, low density, excellent biocompatibility and degradability, and are considered to be one of the most promising bio-based materials. Currently, the three most well-known biomass nanocrystal materials are represented by cellulose nanocrystals, chitin nanocrystals and starch nanocrystals.
[0003] Hemicellulose, a natural polysaccharide, is the second most renewable component of lignin biomass after cellulose, with an annual global production of about 60 billion tons. In softwoods, xylan accounts for a small proportion of total hemicellulose, about 5-15% of the dry weight of the plant. In hardwoods, grasses, and industrial and agricultural byproducts such as cereal straw, bagasse, corn stover, and wood chips, xylan is the main component of hemicellulose, and its skeleton is composed of partially acetylated β-1,4-D-xylopyranose residues. It has been found that xylan acts as a flexible bridge and coating between and around cellulose fibrils, forming the primary and secondary layers of hardwood cell walls. Compared with cellulose, xylan has a lower molecular weight and is easier to extract from biomass, so it has been widely used in the food and cosmetics fields. In addition, xylan can also be used as a polymer matrix to make functional materials and gels.
[0004] Xylan is the most abundant hemicellulose in sugarcane bagasse and is considered a potential substitute for petroleum-based polymers. Deacetylation can form a crystalline structure between xylan and solvent molecules. However, the mechanism behind this is not fully understood, which largely hinders the application of xylan nanocrystals in advanced materials. It is reported that CNC, ChNC and SNC can effectively form and stabilize Pickering emulsions. However, the application of xylan in Pickering emulsions is still in a blank stage.
[0005] In the Chinese patent database, a flexible strain sensor based on conductive hydrogel and its preparation method and application are disclosed, with publication number: CN116183071A, publication date: 20230530. A layer of conductive hydrogel in the flexible strain sensor is sandwiched between two layers of copper foil electrode sheets. The preparation method includes: using graphene oxide, sodium alginate and methacrylamide to prepare a prepolymer solution, heating the prepolymer solution to polymerize into a polymerized hydrogel, soaking it in a calcium chloride solution, rinsing it after soaking and then soaking it in deionized water, and reaching a swelling equilibrium state after sufficient water absorption to obtain a conductive hydrogel; encapsulating the three layers and forming a flexible strain sensor based on a conductive hydrogel.
[0006] The disadvantage of the prior art is that there is no report in the prior art on the use of xylan nanocrystals to prepare a composite hydrogel with strain-resistance effect. Summary of the invention
[0007] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a method for preparing a hydrogel with strain sensing performance from a Pickering emulsion stabilized by xylan nanocrystals, wherein XyNC@pTMPTA microspheres are used as hydrophobic association points to toughen PVA-based hydrogels, and borate bonds are introduced as a dynamic cross-linking network to form a hydrogel with a stable three-dimensional skeleton and strong deformation resistance. The hydrogel has a strain-resistance effect with high sensitivity and high tensile sensitivity.
[0008] The technical scheme adopted by the present invention is: a method for preparing a hydrogel with strain sensing performance from a Pickering emulsion stabilized by xylan nanocrystals, wherein the raw materials for preparation include PVA (polyvinyl alcohol), sodium tetraborate, XyNC (xylan nanocrystals) and TMPTA (trimethylolpropane triacrylate monomer), and the weight ratio of PVA, sodium tetraborate, XyNC and TMPTA is (0.75-1.2): (0.02-0.04): (0.04-0.05): (0.04-0.2);
[0009] The preparation method comprises the following steps:
[0010] (1) dissolving the photoinitiator 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and TMPTA monomer in a solvent of toluene, and then mixing with an aqueous suspension having a XyNC content of 0.4-0.5 wt%, and emulsifying for 1-5 min using a cell crusher in an ice-water bath, wherein toluene is an oil phase and water is an aqueous phase, and the mixture is uniformly mixed to obtain a XyNC@TMPTA emulsion; wherein the amount of the photoinitiator is 0.4-0.55 wt% of the amount of TMPTA;
[0011] (2) placing the obtained emulsion under ultraviolet light for polymerization for 1-5 minutes, so that TMPTA is polymerized into pTMPTA (polytrimethylolpropane triacrylate) to obtain XyNC@pTMPTA microsphere emulsion;
[0012] (3) adding a PVA solution containing sodium tetraborate dissolved in the XyNC@pTMPTA microsphere emulsion;
[0013] (4) After standing to defoam, pour it into a mold and freeze it at a low temperature of -25°C for 12-14 hours. After taking it out, thaw it at room temperature for 2-6 hours. Repeat the freezing and thawing process for more than two times to obtain a multi-network cross-linked PVA hydrogel containing XyNC@pTMPTA composite microspheres, which is the target product. A hydrogel with strain sensing properties is prepared from a Pickering emulsion stabilized by xylan nanocrystals and is named TMPTA-H.
[0014] Furthermore, the XyNC is prepared by grinding dried bagasse to 30-40 mesh, removing fat and wax with an ethanol solution, and then extracting with a 2wt% sodium chlorite solution at 70-80°C for 1 hour to delignify the whole cellulose, and then performing alkali extraction on the obtained whole cellulose to separate the xylan nanocrystals; the alkali extraction is performed by extracting the bagasse with a 1.5-2wt% NaOH solution at 90°C for 2-4 hours, washing and then extracting with a 4wt% NaOH solution for 2-4 hours, and the obtained XyNC is rod-shaped with a size of 20-130nm.
[0015] Furthermore, the weight average molecular weight of the PVA is 10 4 g / mol, and the alcoholysis degree is 98-99%.
[0016] Furthermore, the weight ratio of oil to water in the XyNC@TMPTA emulsion in step (1) is (5:95)-(20:80), and the weight ratio of oil to water is preferably 10:90.
[0017] Furthermore, the freezing and thawing is repeated three times in step (4).
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) Compared with hydrogels containing only PVA physical cross-linked networks, the introduction of pTMPTA microspheres wrapped by XyNC and borate bonds enables chemical cross-linking between the PVA chains and the hydroxyl groups of XyNC on the microsphere surface and borax, thereby enhancing the stability and deformation resistance of the hydrogel three-dimensional skeleton.
[0020] (2) There are two types of characteristic cross-linked networks in the gel system of the present invention. One is the microcrystalline physical cross-linked network formed by the PVA chain through cyclic freeze-thaw cycles, which is the main network to maintain the hydrogel skeleton. The other is the chemical cross-linking between the PVA chain and the hydroxyl group of XyNC on the surface of the microsphere and the borate ester. Thus, a double cross-linked network containing XyNC@pTMPTA microspheres is formed. When subjected to stress changes, the relatively weak BO bond acts as a sacrificial bond, while the hydrophobic association points formed by the hydrophobic effect of the polymer microspheres play a role in dissipating external energy, thereby improving the mechanical properties of the gel. Compared with the mechanical properties of pure PVA hydrogel, the tensile strength and elongation of the product of the present invention are 0.7MPa and 550%, respectively, which are almost 7 and 1.8 times that of pure PVA hydrogel (0.1MPa and 300%).
[0021] (3) The hydrogel has a strain-resistance effect with high sensitivity and high stretch sensitivity, and can be applied to flexible sensors. It not only has good signal stability and durability, but also its conductive sensitivity increases with the increase of the volume fraction of the microspheres, and its sensitivity factor increases from 1.79 to 2.54. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the stress-strain curve diagram of control examples 1-3 and embodiment 1.
[0023] Figure 2 (a) Relative resistance change of control example 2 under (20-100%) strain; (b) Relative resistance change of example 1 under (20-100%) strain; (a′) Change of relative resistance of control example 2 with increasing applied strain; (b′) Change of relative resistance of example 1 with increasing applied strain.
[0024] Figure 3 These are test diagrams of the strain sensor made in Example 1, where (a) is the real-time relative resistance at different frequencies; (b) is the response time of stretching under 5% strain; and (c) is the obtained "XYLAN" Morse code.
[0025] Figure 4 It is the stress-strain curve diagram of Example 1 and Examples 11-15. DETAILED DESCRIPTION
[0026] The technical points of the present invention are described in detail below in conjunction with some specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.
[0027] Example 1
[0028] A method for preparing a hydrogel with strain sensing performance from a Pickering emulsion stabilized by xylan nanocrystals. The raw materials used include: 1 part of PVA, 0.04 part of sodium tetraborate, 0.05 part of XyNC, and 0.04 part of TMPTA.
[0029] The preparation method comprises the following steps:
[0030] (1) The photoinitiator 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and TMPTA monomer are dissolved in a solvent of toluene, and then mixed with an aqueous suspension having a XyNC content of 0.4-0.5 wt %, and emulsified for 1-5 min using a cell crusher in an ice-water bath, wherein toluene is the oil phase, water is the water phase, and the weight ratio of oil to water is 10 / 90; the XyNC@TMPTA emulsion is uniformly mixed, wherein the amount of the photoinitiator is 0.4-0.55 wt % of the amount of TMPTA.
[0031] (2) placing the obtained emulsion under ultraviolet light for polymerization for 1-5 minutes, so that TMPTA is polymerized into pTMPTA to obtain XyNC@pTMPTA microsphere emulsion;
[0032] (3) Adding a PVA solution containing sodium tetraborate dissolved in the XyNC@pTMPTA microsphere emulsion; the weight average molecular weight of the PVA used is 10 4 g / mol, and the alcoholysis degree is 98-99%.
[0033] (4) After standing to defoam, pour it into a mold and freeze it at -25°C for 12 h. After taking it out, thaw it at room temperature for 4 h. Repeat the freezing and thawing three times to obtain a multi-network cross-linked PVA hydrogel containing XyNC@pTMPTA composite microspheres, which is the target product. A hydrogel with strain sensing properties is prepared from a Pickering emulsion stabilized by xylan nanocrystals.
[0034] The XyNC in the above steps is obtained by grinding dried sugarcane bagasse to 30-40 mesh, removing fat and wax with an ethanol solution, and then extracting with a 2wt% sodium chlorite solution at 70-80°C for 1 hour to delignify the whole cellulose, and then performing alkali extraction on the obtained whole cellulose to separate xylan nanocrystals; the alkali extraction is performed by extracting the sugarcane bagasse with a 1.5-2wt% NaOH solution at 90°C for 2-4 hours, washing and then extracting with a 4wt% NaOH solution for 2-4 hours, and the obtained XyNC is rod-shaped with a size of 20-130nm.
[0035] Examples 2 to 10:
[0036] The same steps as in Example 1 were adopted, except that the mass ratios of PVA, sodium tetraborate, XyNC and pTMPTA microspheres were changed, as shown in Table 1 below.
[0037] The mass ratio of PVA, sodium tetraborate, XyNC and pTMPTA microspheres Example 1 1:0.04:0.05:0.04 Example 2 0.75:0.04:0.05:0.04 Example 3 1.2:0.04:0.05:0.04 Example 4 1:0.02:0.05:0.04 Example 5 1:0.03:0.05:0.04 Example 6 1:0.04:0.045:0.04 Example 7 1:0.04:0.05:0.04 Example 8 1:0.04:0.05:0.08 Example 9 1:0.04:0.05:0.1 Example 10 1:0.04:0.05:0.2
[0038] Comparative Example 1
[0039] The strain sensor material of this comparative example is made of the following raw materials: 1 part of PVA.
[0040] The preparation method of the strain sensor of this comparative example comprises the following steps:
[0041] (1) Prepare 10-15 wt% PVA solution with 1 part of PVA and pour it into a mold.
[0042] (2) The gel obtained in step (1) was frozen at -20°C for 12-24 hours, taken out and thawed at room temperature for 2-6 hours, and the freeze-thaw cycles were repeated three times to obtain the PVA-based hydrogel of control example 1.
[0043] The obtained hydrogel was subjected to stress deformation capacity test, and its elongation at break was 295-315%.
[0044] Comparative Example 2
[0045] The strain sensor material of this comparative example is made of the following raw materials: 1 part of PVA and 0.04 part of sodium tetraborate.
[0046] The preparation method of the strain sensor of this comparative example comprises the following steps:
[0047] (1) Dissolve 0.04 g of sodium tetraborate in 1 g of PVA solution (10-15 wt%), let stand to defoam, and pour the solution into molds.
[0048] (2) The gel obtained in step (1) was frozen at -20°C for 12-24 hours, taken out and thawed at room temperature for 2-6 hours, and the freezing and thawing were repeated three times to obtain the hydrogel sample of control example 2. Sodium tetraborate was added to control example 2, so that sodium tetraborate and PVA formed a new cross-linked network structure.
[0049] The obtained hydrogel was subjected to stress deformation capacity test, and its elongation at break was 350-365%.
[0050] Comparative Example 3
[0051] The strain sensor material of this comparative example is made of the following raw materials: 1 part of PVA, 0.04 part of sodium tetraborate, and 0.05 part of XyNC.
[0052] The preparation method of the strain sensor of this comparative example comprises the following steps:
[0053] (1) XyNC suspension (0.4-0.5 wt%) and PVA solution (10-15 wt%) dissolved with sodium tetraborate (0.2-0.4 wt%) were allowed to stand for defoaming and then poured into molds respectively.
[0054] (2) The gel obtained in step (1) was frozen at -20°C for 12-24 hours, taken out and thawed at room temperature for 2-6 hours, and the freezing and thawing were repeated three times to obtain the hydrogel sample of control example 3. Sodium tetraborate and XyNC were added to control example 3, and sodium tetraborate formed hydrogen bonds between XyNC and PVA.
[0055] The obtained hydrogel was subjected to stress deformation capacity test, and its elongation at break was 340-355%.
[0056] Table 2 is a comparison table of the stress-strain capacity of the splines obtained in the above examples.
[0057]
[0058]
[0059] It can be seen from Table 2 above that the required stress-strain capacity can be achieved when the mass ratio of polyvinyl alcohol (PVA), sodium tetraborate, xylan nanocrystals (XyNC), and trimethylolpropane triacrylate microspheres (pTMPTA) is between 0.75-1.2: 0.02-0.04: 0.04-0.05: 0.04-0.2, and the feed ratio can be selected according to actual production needs.
[0060] Embodiment 11-15:
[0061] By adopting the same steps as in Example 1 and changing the amount of solvent toluene, multiple groups of XyNC@TMPTA emulsions with oil-to-water weight ratios of 5 / 95 (Example 11), 8 / 92 (Example 12), 13 / 87 (Example 13), 16 / 84 (Example 14), and 20 / 80 (Example 15) can be obtained. The PVA hydrogel containing XyNC@pTMPTA composite microspheres prepared based on the emulsions with this oil-to-water ratio was subjected to stress testing.
[0062] Table 3 is a comparison table of the stress-strain capacity of the splines obtained in the above examples.
[0063]
[0064]
[0065] It can be seen from Table 3 above that after changing the oil-water ratio of XyNC@pTMPTA microspheres, the stress of Example 1 is the best.
[0066] Figure 1It is the stress-strain curve of control examples 1-3 and example 1. From the figure, it can be seen that the chemical crosslinking of PVA / XyNC / XyNC@pTMPTA microspheres is generated by borate esterification between the hydroxyl groups on the PVA main chain and XyNC and borate, which makes Example 1 have the highest tensile strength.
[0067] Figure 2 The real-time relative resistance changes of the samples of Control Example 2 and Example 1 at different elongation rates (20-100%) and the changes of the relative resistance of the samples with the increase of applied strain. The hydrogel of Example 1 contains XyNC@pTMPTA microspheres, and the GF value is higher than that of the hydrogel of the Control Example, and with the increase of the microsphere content, the GF value also increases to a certain extent, that is, the sensitivity is also the best.
[0068] The hydrogel obtained in Example 1 and the hydrogel obtained in Comparative Examples 1-3 were placed between two electrode sheets to make a strain sensor, and the test was continued.
[0069] Figure 3 The "XYLAN" Morse code obtained by (a) the real-time relative resistance at different frequencies (b) and (c) the response time of the strain sensor under 5% strain of Example 1. It can be seen from the figure that the response time of the strain sensor under 5% strain is only 220ms. In summary, it can be seen that the signal sensitivity of the hydrogel in Example 1 is better when applied to the sensor.
Claims
1. A method for preparing a hydrogel having strain sensing properties from a Pickering emulsion stabilized by xylan nanocrystals, characterized in that: The preparation raw materials include PVA, sodium tetraborate, XyNC and TMPTA, and the weight ratio of PVA, sodium tetraborate, XyNC and TMPTA is (0.75-1.2): (0.02-0.04): (0.04-0.05): (0.04-0.2); The preparation method comprises the following steps: (1) Dissolve the photoinitiator 2-hydroxy-4´-(2-hydroxyethoxy)-2-methylpropiophenone and TMPTA monomer in solvent toluene, and then mix with an aqueous suspension having a XyNC content of 0.4-0.5 wt%, and emulsify for 1-5 min using a cell crusher in an ice-water bath, wherein toluene is the oil phase and water is the water phase, and mix evenly to obtain a XyNC@TMPTA emulsion; The amount of photoinitiator is 0.4-0.55 wt% of the amount of TMPTA; (2) The obtained emulsion is placed under ultraviolet light for polymerization for 1-5 min, so that TMPTA is polymerized into pTMPTA to obtain XyNC@pTMPTA microsphere emulsion; (3) Adding PVA solution containing sodium tetraborate dissolved in the XyNC@pTMPTA microsphere emulsion; (4) After standing to defoam, pour it into a mold and freeze it at -25 °C for 12-14 h. After taking it out, thaw it at room temperature for 2-6 h. Repeat the freezing and thawing process for more than two times to obtain a multi-network cross-linked PVA hydrogel containing XyNC@pTMPTA composite microspheres, which is the target product. The hydrogel with strain sensing properties is prepared from the Pickering emulsion stabilized by xylan nanocrystals.
2. The method for preparing a hydrogel having strain sensing performance from a Pickering emulsion stabilized by xylan nanocrystals according to claim 1, characterized in that: The XyNC is prepared by grinding dried bagasse to 30-40 mesh, removing fat and wax with an ethanol solution, and then extracting with a 2 wt% sodium chlorite solution at 70-80°C for 1 hour to delignify the whole cellulose, and then performing alkali extraction on the obtained whole cellulose to separate xylan nanocrystals; the alkali extraction is performed by extracting the bagasse with a 1.5-2 wt% NaOH solution at 90°C for 2-4 hours, washing and then extracting with a 4 wt% NaOH solution for 2-4 hours. The obtained XyNC is rod-shaped and has a size of 20-130 nm.
3. The method for preparing a hydrogel having strain sensing performance from a Pickering emulsion stabilized by xylan nanocrystals according to claim 1, characterized in that: The weight average molecular weight of the PVA is 10 4 g / mol, and the degree of alcoholysis is 98-99%.
4. The method for preparing a hydrogel having strain sensing performance from a Pickering emulsion stabilized by xylan nanocrystals according to claim 1, characterized in that: The oil-water weight ratio of the XyNC@TMPTA emulsion in step (1) is (5:95)-(20:80).
5. The method for preparing a hydrogel having strain sensing performance from a Pickering emulsion stabilized by xylan nanocrystals according to claim 4, characterized in that: The oil-to-water weight ratio is 10:
90.
6. The method for preparing a hydrogel having strain sensing performance from a Pickering emulsion stabilized by xylan nanocrystals according to claim 1, characterized in that: In step (4), freeze-thaw was repeated three times.
Citation Information
Patent Citations
Flexible strain sensor based on conductive hydrogel and preparation method and application thereof
CN116183071A
Dual-network nanocomposite hydrogel based on xylan as well as preparation method and application of dual-network nanocomposite hydrogel
CN106279542A
Preparation method of photo-crosslinking polyvinyl alcohol / nanocrystalline cellulose PVA / CNC compound hydrogel
CN107033371A
Preparation method of ionic conductive hydrogel, ionic conductive hydrogel and application
CN116162264A
Cellulose nanocrystal composite multifunctional flexible hydrogel as well as preparation method and application thereof
CN118978714A
Cited By
Composite hydrogel and preparation method thereof
CN120484284A